Developing Geometrical Reasoning among Children at Secondary Level - Sreedharacharyulu, K.; Singh, Sardar Dharmendra (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Mathematics is the most beautiful subject among all of the subjects in the school curriculum. The beauty of mathematics can be enjoyed because of its nature of having reasoning. The beauty is enriched even more when we deal with geometry. Geometrical reasoning is not only useful for making difficult problems solving easy but also it gives pleasure to human brain to have more joy. The present paper is theoretical paper which discusses on classroom strategies in developing geometrical reasoning among children at secondary level. These strategies may be project based teaching learning process, ICT based teaching learning process (especially with geogebra) and digital games like ―Police squad‖ and some hands on activities etc.